High-intensity interval training and high-intensity resistance training on body fat percentage and aerobic fitness among female overweight adults / Asfarina Jitwil, Patricia Pawa Pitil and Wan Juliana Emeih Wahed - Jitwil, Asfarina; Pitil, Patricia Pawa; Wahed, Wan Juliana Emeih (Faculty of Sport Science and Recreation, Universiti Teknologi MARA, 2019)
The prevalence of overweight or obesity has increased worldwide and this was associated with increased risk factors for cardiovascular disease. Studies also had suggested that individuals with the high accumulation of body fat in the abdominal region were at greater risk of developing metabolic syndrome. Existing studies had not directly studied a comparable amount of high-intensity interval training (HIIT) and high-intensity resistance training (HIRT) on the improvement of body composition and aerobic fitness. The purpose of this study was to compare the effects between 6 weeks of HIIT and HIRT on body fat percentage and aerobic fitness among overweight female adults. Fourteen sedentary female were recruited and assigned to two groups; HIIT (n = 7) and HIRT (n = 7), aged 22.571 ± 1.399 years, height 155.929 ± 2.841cm, weight 63.464 ± 5.873 kg and BMI 26.079 ± 2.032 kg/m2. Both training interventions were conducted with 90% of heart rate maximum which included 12 types of bodyweight exercises performed 30 seconds with 10 seconds of transition time between bouts of exercises for 2 -3 sets for HIIT and 75% of 1-RM for HIRT consisting of compound of push and pull exercises targeting large muscle groups of 10 repetitions for 3 sets with 2 minutes rest interval. The results showed that there were significant differences in body fat percentage (p < .05) and aerobic fitness (p < .05) in both training programs. In comparing the two trainings, HIRT produced greater significant improvement in aerobic fitness than HIIT. However, body fat percentage did not differ significantly between these trainings (p > .05). In conclusion, both HIIT and HIRT were effective in reducing body fat percentage and improving aerobic fitness among overweight female adults.